Effects of Holocene climate changes on alpine ecosystems: Nonequilibrium dynamics drive insect species richness on alpine islands. (1st July 2019) - Marta, Silvio; Lacasella, Federica; Cesaroni, Donatella; Sbordoni, Valerio
Abstract: Aim: To identify the effect of multiple, temporally close, forcing events (i.e. climate‐driven habitat fragmentations/homogenizations) in shaping current patterns of biodiversity in alpine areas. Given their spatial configuration, alpine areas have been traditionally seen as islands surrounded by an "ocean" of unsuitable lands. A quantitative assessment of the effects of Holocene climate fluctuations on islands area and inter‐island connectivity is crucial to finely reconstruct past biodiversity dynamics and forecast species responses to future changes. Location: Italy. Taxa: Carabidae (Ground beetles), Chrysomelidae (Leaf beetles), Elateridae (Click beetles), Orthoptera (Grasshoppers and Crickets) and Papilionoidea (Butterflies and Skippers). Methods: A total of 1, 077 species for 128, 093 records were analysed and a classification based on their functional traits allowed identifying groups of good and poor dispersers within each taxon. A dynamic discrete model of ecosystem evolution provided the spatio‐temporal context to test two competing (transient equilibria vs. nonequilibrium) dynamics based on different colonization capabilities. In the transient equilibria dynamic the species are able to respond to island evolution through successful dispersal and colonization events, whereas in the nonequilibrium dynamic ineffective immigration constrains the current species richness to that generated by the strongest island contraction. Results: With the exception of Elateridae, good dispersers (Chrysomelidae and Papilionoidea) responded to environmental changes by establishing a series of transient equilibria. In contrast, the nonequilibrium dynamic better described patterns of species richness in poor dispersers (Carabidae and Orthoptera). Main conclusions: Our approach could be used as the basis for the development of spatially and temporally explicit models of island evolution and could be a valuable tool for quantifying the sensitivity of single taxa to climate‐driven habitat changes. It also represents a further step towards the forecasting of future responses to climate change and the accompanying development of conservation strategies that more effectively respond to the detrimental impacts of climate change on biodiversity.